COMPARATIVE ANALYSIS ON THE PROFITABILITY OF SOLE MAIZE CROPPING AND MAIZE/MELON INTERCROP IN OSUN STATE, NIGERIA - Baruwa, Isiaka Olayinka; Familusi, Ife Gideon (Journal of Agricultural Sciences (Belgrade), 2018)
Profitability is a motivational factor in any enterprise. The study compared the profitability of sole maize and maize/melon intercrop in Osun State. Purposive sampling technique was used and primary data collected with the aid of a structured questionnaire Descriptive statistics, budgetary technique, inferential statistics and regression techniques were used to analyse the data collected. Majority of the respondents were in their active ages, male, had formal education and had less than 21 years of experience in cropping system. The estimated net return to management was N 59,323.83 per sole maize farmer or N 37,548.75 per hectare per year and N 175,178.68 per farmer or N 102,832.17 per hectare for maize/melon. Budgetary analysis results showed that both sole maize and maize/melon intercrop were profitable. The multiple regressions for maize/melon intercrop revealed that 94.2% of variation in profit was obtained by independent variables in the model. The multiple regressions for the sole maize profit function revealed that 62.3% of variation in profit was obtained by independent variables in the model. The costs of input used, labour employed and quantity sold were the major determinants of profitability. The appropriate policies to enable the farmers have access to inputs at subsidized rate should be put in place.
Keywords: Sole cropping; regression; profitability; Maize; Intercropping; Farmers